Large and active CO2 uptake by coupled carbonate weathering - Liu, Zaihua; Macpherson, G.L.; Groves, Chris; Martin, Jonathan B.; Yuan, Daoxian; Zeng, Sibo (Earth-science reviews, 2018)
Carbonate mineral weathering coupled with aquatic photosynthesis on the continents, herein termed coupled carbonate weathering (CCW), represents a current atmospheric CO2 sink of about 0.5 Pg C/a. Because silicate mineral weathering has been considered the primary geological CO2 sink, CCW's role in the present carbon cycle has been neglected. However, CCW may be helping to offset anthropogenic atmospheric CO2 increases as carbonate minerals weather more rapidly than silicates. Here we provide an overview of atmospheric CO2 uptake by CCW and its impact on global carbon cycling. This overview shows that CCW is linked to climate and land-use change through changes in the water cycle and water-born carbon fluxes. Projections of future changes in carbon cycling should therefore include CCW as linked to the global water cycle and land-use change.